2015
DOI: 10.1097/aln.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Output and Cerebral Blood Flow

Abstract: Cerebral blood flow (CBF) is rigorously regulated by various powerful mechanisms to safeguard the match between cerebral metabolic demand and supply. The question of how a change in cardiac output (CO) affects CBF is fundamental, because CBF is dependent on constantly receiving a significant proportion of CO. The authors reviewed the studies that investigated the association between CO and CBF in healthy volunteers and patients with chronic heart failure. The overall evidence shows that an alteration in CO, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
152
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(160 citation statements)
references
References 77 publications
5
152
2
1
Order By: Relevance
“…Although LV remodeling starts at the onset of MI, clinical manifestation of chronic heart failure may not develop for years in humans given the progressive maladaptive remodeling that may continue for a lifetime [20]. Multiple studies revealed the association between CO and CBF in both healthy and cardiac impaired individuals linking heart failure mediated low CO to CBF reduction [4,6–10]. However, no studies assessed the impact of early (day 1) till late stages (30 days) of acute cardiac injury post MI, on CBF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although LV remodeling starts at the onset of MI, clinical manifestation of chronic heart failure may not develop for years in humans given the progressive maladaptive remodeling that may continue for a lifetime [20]. Multiple studies revealed the association between CO and CBF in both healthy and cardiac impaired individuals linking heart failure mediated low CO to CBF reduction [4,6–10]. However, no studies assessed the impact of early (day 1) till late stages (30 days) of acute cardiac injury post MI, on CBF.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that in the first and second stages of cardiac remodeling post-MI, regulatory mechanisms limit the impact of CO on CBF. In fact, CBF is an integrative and complex process combining the function of multiple systems including pulmonary gas exchange, cardiovascular function, and intracranial cerebrovascular regulators [3,4]. MI impact on cerebral perfusion is multifaceted and not only mediated through CO alteration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations